CLINICAL INVESTIGATION OF INCISIONAL HERNIA FOLLOWING RUNNING MASS CLOSURE OF THE ABDOMEN USING ABSORBABLE SYNTHETIC MONOFILAMENT LOOPED SUTURES - KAWAMOTO, Koichi; YOON, Hyung-Eun; HIGAKI, Jun; KIN, Keiwa; MIKATA, Shoki; NISHITANI, Akiko; KAMIIKE, Wataru; OIMATSU, Natsumi; MIYAZAKI, Minoru; HOASHI, Takaya; IWASE, Kazuhiro (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2003)
We studied the clinical features of an incisional hernia following running mass closure of abdominal midline incisions using absorbable synthetic monofilament sutures. Subjects were 588 cases followed up at least 1.5 years. Incisional hernia was recognized in 22 cases (3.7%): within 3 months after surgery in 4, between 3 and 6 months in 6, between 6 and 9 months in 4, between 9 and 12 months in 3, exceeding 1 year in 4. Herniation started around the umbilicus in 55% of cases with an incisional hernia, and around a suture knot in 38%. Synthetic monofilament suture absorption at the hernial incision was considered negligible. Caution should therefore be paid when suturing around the umbilicus during running mass closure of abdomen.